The Novel as Investigation : Leonardo Sciascia, Dacia Maraini, and Antonio Tabucchi - Cannon, JoAnn (Book collections on Project MUSE., 2006)
"Detective fiction is a universally popular genre: stories about crime investigation are published all over the world and in hundreds of languages. However, detective fiction provides more than entertainment; it often has a great deal to say about important social issues such as crime and punishment, justice and injustice, testimony and judgment. The Novel as Investigation examines a group of detective novels published from the mid-1980s to the end of the century by three Italian writers - Leonardo Sciascia, Dacia Maraini, and Antonio Tabucchi - whose commitment to ethical responsibility informs much of their work."--Jacket.